Empathy-Based Problem-Based Learning in Teaching Inspirational Story Texts at the Elementary School Level - Ngainun Ni'mah; Kms. Muhammad Amin Fauzi (Journal of Elementary Education Research and Practice, 2026)
This study explores how Problem-Based Learning (PBL) supports empathy-based interpretation and character-oriented literacy in teaching inspirational story texts at the elementary school level. Previous studies have often examined PBL in relation to comprehension, participation, or textual analysis, while limited attention has been given to its role as a pedagogical mechanism that connects empathy, moral interpretation, written reflection, and character formation. Using a qualitative embedded single-case study design, this research was conducted in a Grade VI Indonesian language classroom consisting of 25 students, with 14 main informants selected through purposive and maximum variation sampling. Data were collected through interviews, focus group discussions, classroom observations, and document analysis, and were analyzed thematically. The findings show that contextual problem orientation stimulated students’ empathy before textual analysis, collaborative discussion supported moral interpretation, and teacher scaffolding helped students develop written reflections. The study identifies an empathy-based PBL mechanism in which contextual problems stimulate empathy, empathy encourages collaborative critical discussion, and discussion strengthens moral interpretation, written reflection, and character formation. The findings suggest that PBL can function as an integrative approach for connecting literacy, empathy, writing, and character education in elementary Indonesian language learning.